(untitled) (Baghdad Science Journal, 2011)
The study included the collection of 75 bronchial wash samples from patients suspected to have lung cancer. These samples were subjected to a diagnostic cytological study to detect the dominant type of lung cancer. It was noticed that 33 patients proved to have a lung cancer out of 75 (44%) of these, 19 cases (57.6%)were diagnosed having Squamus cell carcinoma,7cases (21.21%) showed Adenocarcinoma ,6 cases (18.18%) were having small cell carcinoma while only one case (3.03%)was large cell carcinoma .Nearly 70% of cases were correlated with smokers .Bacteria were isolated from 53 patients in which 33 isolates were associated with the cancer cases while 20 of them from non infected patients. By using different morphological ,biochemical tests followed by api20 ,the bacterial isolates correlated with cancer were diagnosed and were characterized as 12 isolates (36.36%) of Pseudomonas aeruginosa ,6 isolates (18.18%) were Klebsiella pneumoniae ,Pseudomonas fluorescence and Esherichia coli for each while only 3 isolates (9.09%)of Acinetobacter baumannii were isolated. Some of bacterial virulence factors were determined in which,24 isolates (72.7%) were capable of agglutinating red blood cells, 16 isolates (48.5%) had the ability to adhere to epithelial cells , in addition ,15 isolates (45.5%) proved to have capsule and 24 isolates(72.7%) gave a positive results in heamolysin test beside ,25 isolates (75.8%) were ß –Lactamase producers. The isolates were highly resisted Ampicillin, Amoxicillin and Cefotaxime while they were inhibited by low concentrations of Ciprofloxacin and Cefepime the 4th generation cephalosporins.